Percepções sobre o ensino de filosofia registros de um tempo e seus movimentos - Rodrigues, Augusto (Editora Oficina Universitária, 2022)
Written by many hands, this work is a collection that brings together 14 chapters around the theme of philosophy teaching. Teachers and researchers collaborated with their texture, for whom teaching philosophy is a genuine philosophical problem, as they consider that it is by thinking about the relationships between philosophy and its teaching that we are also in a position to problematize our training and performance as teachers. of philosophy and philosophers in contemporary times. If the teaching of philosophy represents the background of the chapters, the common thread is the shared experiences of the Study and Research Group on Teaching Philosophy (ENFILO). The work was divided into four parts. The first, The teaching of philosophy: questions from/to the scientific-philosophical field, presents chapters by Patrícia Del Nero Velasco and Elisete M. Tomazetti, produced in interface and tension with research in the area in Brazil. The second part, Philosophy teaching and training, concentrates the chapters built around the restructuring of the philosophy course at UNESP. Augusto Rodrigues, Rodrigo Pelloso Gelamo, Amanda Velloso Garcia, Bruna de Jesus Silva, Elói Maia de Oliveira, Júlio César Rodrigues da Costa show, from different perspectives, their political-philosophical participation, their questioning of the structure of the course, their claims for another teacher training and for a teaching of philosophy that is up to the challenge of contemporary times. In the third part, Formative Legacies, research by José Roberto Sanabria de Aleluia and Tiago Brentam Perencini is presented, which are developed around the institutionalization of university philosophy teaching in Brazil. In the last part, Teaching Philosophy and Experience, Genivaldo de Souza Santos, Daniel Salésio Vandresen, Silmara Cristiane Pinto, Sara Moraes Rosa, Rodrigo Barbosa Lopes present their research that emerges, mainly, from the tensions created with the exercise of teaching philosophy in contemporary times.